A Review of Renewable Energy Laws in Malaysia: Comparing solar energy policies in Malaysia, United States, and China. Issue 7 (2022) - Harizal, Muhammad Al Hariz; Noor, Nur Syafiqah Mohd; Anuar, Nurin Irdina Khairol
No abstract available